Development of E-Based Learning Modules Problem Based Learning (PBL) in improving students' critical thinking abilities - Anggi, Anggi; Agung Saputra, Rizka Donny; Rahmawati, Fitri (JUPE : Jurnal Pendidikan Mandala, 2024)
This research aims to determine the feasibility of problem-based learning (PBL) e-Modules in improving students' critical thinking skills. The research carried out is a type of R&D (Research and Development) research that follows the 4D development model. This research was carried out at the Al-Ikhlas Taliwang Islamic Boarding School for class XI students. This research will last for three months, starting from December to February 2023/2024. Determination of the sample in this research was carried out using purposive sampling technique. The number of samples in this study was 26 students from class XI. Data collection techniques in this research are observation, interviews, documentation and questionnaires. The research instrument consists of a material expert validity test questionnaire, a media expert validity test questionnaire, and an e-module readability test questionnaire by students. The data analysis technique uses the average percentage score formula from the validation results of material experts and media experts, and the results of e-module readability tests by students. From the results of the material expert validation, a score of 3.3 was obtained from validator 1 and 3.6 from validator 2, an average score of 3.45 with good criteria. Then the media expert validation results obtained a score of 3.5 from validator 1 and 3.4 from validator 2 with an average score of 3.45 with good criteria. Based on the results of the e-module readability test assessment by students, it shows that the results of the class . So it can be said that the e-module that is being developed is practical for use in learning.